Penerapan Analisis Jalur Pengaruh Kualitas Layanan Akademik Terhadap Loyalitas Melalui Kepuasan Mahasiswa - Khairun IT. Aluy; Emli Rahmi; Dewi Rahmawaty Isa; Friansyah Gani (Transbahasa, 2026)
Student loyalty is an important indicator of institutional sustainability and competitiveness in higher education. One factor that influences student loyalty is the quality of academic services provided by universities. High-quality academic services can improve students’ learning experiences and increase their satisfaction, which in turn may strengthen their loyalty to the institution. This study aims to analyze the effect of academic service quality on student loyalty, with student satisfaction acting as a mediating variable. This research employs a quantitative approach using path analysis to examine both the direct and indirect relationships among the variables. Data were collected from university students through questionnaires measuring perceptions of academic service quality, student satisfaction, and student loyalty. The results show that academic service quality has a significant direct effect on student loyalty with a coefficient value of 0.327. In addition, academic service quality has a significant indirect effect on student loyalty through student satisfaction with a coefficient value of 0.241. These findings indicate that better academic service quality leads to higher student satisfaction, which subsequently enhances student loyalty toward the institution. The study emphasizes the importance of continuously improving academic service quality in order to create better learning experiences and strengthen student loyalty in higher education institutions.